Switched Delay Line Microwave Reconfigurable Filter - Wong, Peng Wen (2008)
A novel electronically reconfigurable microwave bandpass filter based on switched delay line approach is presented. In contrast to conventional tunable filters, the approach enables the lossy and non-linear switching elements to be used as part of the coupling elements rather than within the resonators. Therefore the filter distinguishes itself through its ability to provide a wide tuning bandwidth with low passband loss and high linearity. Theoretical analysis of the approach is presented in this paper. The feasibility of the approach has been experimentally verified with microstrip circuit prototype. The filter produced a maximum passband loss of 1.7 dB and an IP3 of >32 dBm with 35% tuning bandwidth.